THE EFFECTS OF STUDENT'S PERCEPTION ON LEARNING TECHNIQUE AND LEARNING MOTIVATION ON STUDENTS' SPEAKING SKILLS - Okke Tri Wahyuni (INFERENCE: Journal of English Language Teaching, 2021)
Abstract: This research aims to know the effect of students' perception on learning technique and learning motivation towards students' speaking skills. The research methodology is a descriptive survey and using a questionnaire as data collection. The number of the samples is three classes from two state vocational high schools. The result of the research shows that; 1). There is a significant effect of students' perception on learning technique and learning motivation jointly toward students' speaking skills. The score of Sig proves that 0,000 < 0,05 and F0 = 47.152. Both variables, student's perception of learning technique and learning motivation, had contributed 62.3 % to the student's speaking skill. 2). There is a significant effect of student's perception on learning technique toward the student's speaking skill. The score of Sig proves 0,000 < 0,05 and t0 = 4.555. 3). There is a significant effect of the learning motivation towards the student's speaking skills. It is proved by Sig. = 0,000 < 0,05 and t0 = 4,528. Having a good perception of learning techniques and high learning motivation will improve student's speaking skills better.Keywords: student's perception, learning technique, motivation, speaking skill.